Rancang Bangun Alat Fiksasi Cassette Holder pada Pemeriksaan Vertebrae Cervical Proyeksi Lateral dengan Kondisi Pasien Non Kooperatif - Khairunisa Octine Wahyudi; Dina Widyasari; Anshor Nugroho (Pusat Riset dan Inovasi Nasional, 2026)
A noncompliant patient is one who cannot adhere to instructions or collaborate with healthcare professionals throughout the assessment. A fixation aid is employed to help the radiographer in attaining appropriate positioning of the patient and the cassette, thus guaranteeing optimal radiographic outcomes. This study employed an experimental methodology through the research and development strategy. The cassette holder fixation device was evaluated on five radiographers. Data collection was conducted through functional and performance assessments of the cassette holder at RSUD (Regional General Hospital) Muntilan and Dr. Soeharso Hospital in Surakarta from December 2024 to August 2025. The evaluation employed a checklist questionnaire for radiographers. The cassette holder fixation device was designed and modified into a U-shape, serving as a cassette support, with the base providing stability for the holder. The cassette holder fixation device features a locking mechanism and includes an adjustable left-hand cassette support to accommodate various cassette sizes. The cassette holder fixation device is applicable for lateral projection studies of cervical vertebrae. The cassette holder fixation device is constructed from 0.5 cm thick acrylic. The outcomes of functional testing indicated an 86% success rate, above the minimum feasibility threshold of 75%. This illustrates that the cassette holder fixation device is efficient in stabilizing the cassette, reducing radiation exposure to the radiographer, patient, and family, and optimizing cervical spine examination duration. The cassette holder fixation device enhances stability for both the cassette and the examination object, thereby reducing the probability of repeat imaging and preventing patients from receiving double radiation exposure.